EVOLUTION OF AGRICULTURAL TRADE IN THE PERIOD 2010-2017. CASE STUDY - ROMANIA - Liviu MARCUTA; Alina MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Agricultural insurance is rightly considered by both researchers and practitioners as one of the main methods of managing risks in agriculture. However, a unanimous conception of agricultural risk classification has not been established in the literature. There are divergences of opinion regarding the systematization of clear criteria for grouping agricultural risks, and the risk be useful for both agrarian entrepreneurs and especially for managers groups are not integrated into a classification. In the author's opinion, such systematization will of insurance companies, who provide agricultural risks. Based on this systematization, advantageous insurance offers can be developed for agricultural producers because the insurance companies in the Republic of Moldova offer separate insurance products, mostly those that are subsidized by the state.